Casino Gaming In Singapore: A "must have"? - Jeyasingam, Shanthi (2007)
The purpose of this research is to investigate the Integrated Resort and Casino proposal for Singapore. Singapore has set herself a Tourism 2015 goal that includes the following: doubling visitor arrivals to 17 million and tripling tourism receipts to S$30 billion. In keeping with this, Singapore has proposed and confirmed the decision to build an Integrated Resort and Casino.